2015
DOI: 10.1128/aac.04844-14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Raltegravir or Elvitegravir Resistance Signature Mutations on the Barrier to Dolutegravir Resistance In Vitro

Abstract: cThe recently approved HIV-1 integrase strand transfer inhibitor (INSTI) dolutegravir (DTG) (S/GSK1349572) has overall advantageous activity when tested in vitro against HIV-1 with raltegravir (RAL) and elvitegravir (EVG) resistance signature mutations. We conducted an in vitro resistance selection study using wild-type HIV-1 and mutants with the E92Q, Y143C, Y143R, Q148H, Q148K, Q148R, and N155H substitutions to assess the DTG in vitro barrier to resistance. No viral replication was observed at concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Interestingly, the selection of E92Q/ N155H/R263K in response to EVG was reported in that study (18), and we show here that this virus is highly resistant to this INSTI.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, the selection of E92Q/ N155H/R263K in response to EVG was reported in that study (18), and we show here that this virus is highly resistant to this INSTI.…”
Section: Discussionmentioning
confidence: 62%
“…While resistance mutations were detected within 29 weeks under either DTG or EVG selection pressure, no resistance mutations emerged under pressure with RAL. A direct comparison cannot be drawn between our selection studies, which were performed using rhesus PBMCs, and those performed by others who used HIV-1 in MT-2 cell lines and showed that mutations emerged rapidly under RAL pressure (31,46). Our selection experiments with RAL may suggest that RAL possesses a higher genetic barrier than the other INSTIs in rhesus macaques; however, a previous study revealed that SHIV-infected macaques treated with pressure from L-870812, a RAL analogue, possessed the N155H substitution after 25 days of treatment with this drug (36).…”
Section: Discussionmentioning
confidence: 70%
“…Thus cross-resistance exists between RAL and EVG in regard to mutations at positions 155 and 148. In contrast, DTG has a higher barrier to HIV drug resistance than do RAL and EVG (White et al 2014;Llibre et al 2015;Seki et al 2015;Wainberg and Han 2015). The major mutations that confer resistance to RAL, EVG, and DTG are summarized in Table 1.…”
Section: The Unique Hiv Drug Resistance Profile Of Dtgmentioning
confidence: 99%